A Randomized Trial Comparing Seven-Day Ranitidine Bismuth Citrate and Clarithromycin Dual Therapy to Seven-Day Omeprazole, Clarithromycin and Amoxicillin Triple Therapy for the Eradication of Helicobacter pylori - Sander Veldhuyzen van Zanten; Naoki Chiba; Alan Barkun; Carlo Fallone; Alain Farley; Alan Cockeram; Chrystian Dallaire; Lorinda Simms; Barbara Nicholls (Canadian Journal of Gastroenterology)
OBJECTIVE: To assess Helicobacter pylori eradication after one week dual ranitidine bismuth citrate-clarithromycin (RBC-C) or triple omeprazole, clarithromycin and amoxicillin (OCA) therapy.